Kewenangan Hakim Untuk Menetapkan Penangguhan Penahanan Sementara Terhadap Terdakwa Dalam Pemeriksaan Perkara Pidana Berdasarkan Kuhap - Muclas Ade Putra (JOURNAL of LEGAL RESEARCH, 2022)
In order for the judge to be able to investigate the defendant's case, the judge has the authority to detain the defendant. In addition, the judge is in the best position to determine whether or not the defendant should have his or her detention suspended before the case is decided by the court. This authority comes from the judge's intimate familiarity with the case. The suspension of the detention of the suspect or defendant from his or her family, the existence of guarantees against the suspect or defendant in the form of money or people in the suspension of detention, and the judge's belief that, according to Article 21 paragraph (1) of the Criminal Procedure Code, the suspect or defendant will not flee, will not damage evidence, and will not commit the crime again are all factors that can lead to a judge granting a suspension of detention.